BreastScreen Australia national data by factors of interest for risk‐based screening: routinely reported data and opportunities for enhancement - Chelsea Carle; Louiza S. Velentzis; Carolyn Nickson (Elsevier, 2022)
Abstract Objective: There is growing interest in more risk‐based approaches to breast cancer screening in Australia. This would require more detailed reporting of BreastScreen data for factors of interest in the assessment and monitoring of risk‐based screening. This review assesses the current and potential availability and reporting of BreastScreen data for this purpose. Methods: We systematically searched governmental BreastScreen reports and peer‐reviewed literature to assess current and potential availability of outcomes for predetermined factors including breast cancer risk factors and factors important for implementing, monitoring or evaluating risk‐based screening. Outcomes evaluated were BreastScreen Performance Indicators routinely included in BreastScreen Australia monitoring reports, and key tumour characteristics. Results: All outcomes were reported annually by age group, except for tumour hormone receptor status, nodal involvement and grade. Screening participation was reported nationally for many factors important for risk‐based screening; other reporting was ad hoc or unavailable. Conclusions: There is potential to build on BreastScreen's existing high‐quality national data collection and reporting systems to inform and support risk‐based breast screening. Implications for public health: Enhanced BreastScreen data collection and reporting would improve the evidence base and support evaluation of risk‐based screening and improve the detail available for benchmarking any future changes to the program.